The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00228-018-2420-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of pharmacokinetic interaction between fluvastatin and green tea in healthy volunteers

Abstract: Although in vitro studies indicated that EGCG and brewed green tea produce significant inhibitory effects on CYP2C9 activity, the concomitant administration of green tea and fluvastatin in healthy volunteers did not influence the pharmacokinetics of fluvastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In an in vitro study, it has been demonstrated that 0.1 – 100 µM of EGCG inhibits CYP2C9 activity, and subsequently suppresses fluvastatin degradation in an EGCG-concentration dependent manner. However, a subsequent clinical study reported no significant differences in C max , AUC, and t 1/2 of fluvastatin in human subjects who were co-administered brewed green tea and GTE 36 . It is important to note that this study did not investigate the specific effect of EGCG on fluvastatin in human subjects.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In an in vitro study, it has been demonstrated that 0.1 – 100 µM of EGCG inhibits CYP2C9 activity, and subsequently suppresses fluvastatin degradation in an EGCG-concentration dependent manner. However, a subsequent clinical study reported no significant differences in C max , AUC, and t 1/2 of fluvastatin in human subjects who were co-administered brewed green tea and GTE 36 . It is important to note that this study did not investigate the specific effect of EGCG on fluvastatin in human subjects.…”
Section: Methodsmentioning
confidence: 95%
“…It is important to note that this study did not investigate the specific effect of EGCG on fluvastatin in human subjects. Based on the findings, the research team concluded that a single administration of green tea or EGCG is unlikely to cause clinically significant interactions with fluvastatin [36].…”
Section: Epigallocatechin Gallate Increases Plasma Concentrations Of ...mentioning
confidence: 99%
“…A single oral dose of 30 mg nadolol (Nadic®, Sumitomo Dainippon Pharma, Osaka, Japan) was administered in the morning of the study day with 150 mL of concomitant brewed green tea, or 1 hour after 150 mL of brewed green tea or with 150 mL of concomitant water. Brewed green tea was prepared before ingestion in every trial according to previous studies 11,12 in order to achieve an EGCG concentration of approximately 100 mg dL −1 . In brief, commercially available green tea leaves (3.0 g per 100 mL, Harada Tea Processing Co. Ltd., Shimada, Japan) were mixed with hot water (90°C) for 4 minutes with stirring 1 day before the clinical trial, and the brewed green tea was stored at 4°C until the subjects took it.…”
Section: Methodsmentioning
confidence: 99%
“…As evidenced by clinical studies, the significant degree of variability in the pharmacokinetic parameters of EGCG might be explained by genetic variations in the genes encoding the drug transporters MRP2 and organic anion transporter SLC21A6 (OATP1B1). It is possible that this interindividual heterogeneity could account for the quantities of green tea polyphenols in human plasma or their potential to induce beneficial effects [ 364 ] and their potential to trigger pharmacokinetic interaction with other drugs [ 365 , 366 , 367 , 368 ].…”
Section: Egcg In Cancer Prevention and Therapy?mentioning
confidence: 99%